Determinan kualitas laporan keuangan pemerintah daerah Kota Surabaya - Ayu Ningrum, Sita; Sundari, Siti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to examine the effect of the implementation of good governance, competence of the apparatus, and the government's internal control system on the quality of the Surabaya City Government's financial reports. The research method used is quantitative. The object of this research is all Regional Apparatus Organizations (OPD) in the form of services and agencies of the Surabaya City Government. The research population includes 207 government officials and agencies involved in financial management in the Surabaya City Government. The sampling technique used is simple random sampling method. Data collection was carried out by distributing questionnaires, while the data analysis technique used SEM PLS with SmartPLS software. The results of this study indicate that the implementation of good governance, the competence of the apparatus and the government's internal control system have contributed to the quality of the financial reports of the Surabaya City Government. This shows that the higher the implementation of good governance, the competence of the apparatus and the government's internal control system, the quality of the financial reports of the Surabaya City government will increase.